Heart and Nervous System Pathology in Compound Heterozygous Friedreich Ataxia. Issue 8 (20th July 2017) - Becker, Alyssa B.; Qian, Jiang; Gelman, Benjamin B.; Yang, Michele; Bauer, Peter; Koeppen, Arnulf H.
Abstract: In a small percentage of patients with Friedreich ataxia (FA), the pathogenic mutation is compound heterozygous, consisting of a guanine–adenine–adenine (GAA) trinucleotide repeat expansion in one allele, and a deletion, point mutation, or insertion in the other. In 2 cases of compound heterozygous FA, the GAA expansion was inherited from the mother, and deletions from the father. Compound heterozygous FA patient 1, an 11-year-old boy (GAA, 896/c.11_12TCdel), had ataxia, chorea, cardiomyopathy, and diabetes mellitus. Compound heterozygous FA patient 2, a 28-year-old man (GAA, 744/exon 5 del), had ataxia, cardiomyopathy, and diabetes mellitus. Microscopy showed cardiomyocyte hypertrophy, iron-positive inclusions, and disrupted intercalated discs. The cardiac lesions were similar to those in age-matched homozygous FA patients with cardiomyopathy and diabetes mellitus (boy, 10, GAA 1016/1016; woman, 25, GAA 800/1100). The neuropathology was also similar and included hypoplasia of spinal cord and dorsal root ganglia, loss of large axons in dorsal roots, and atrophy of the dentate nucleus (DN). Frataxin levels in heart and DN of all 4 FA cases were at or below the detection limits of the enzyme-linked immunosorbent assay (≤10 ng/g wet weight) (normal DN: 126 ± 43 ng/g; normal heart: 266 ± 92 ng/g). The pathologic phenotype in homozygous and compound heterozygous FA is determined by residual frataxin levels rather than unique mutations.